Insulin-like growth factor binding protein 2 (IGFBP-2) as prognostic parameter in infarct-related cardiogenic shock - Masyuk, Maryna; Wernly, Bernhard; Kelm, Malte; Freund, Anne; Pöss, Janine; Desch, Steffen; Schneider, Steffen; Akın, Ibrahim; Fürnau, Georg; Ceglarek, Uta; Schemmelmann, Mara; Isermann, Berend; et al. (International journal of cardiology, 2026)
Background - Cardiogenic shock (CS) caused by acute myocardial infarction (AMI) is a critical condition with high mortality rate. Insulin-like growth factor binding protein 2 (IGFBP-2) is dysregulated in cardiovascular diseases. The purpose of the present study was to investigate the prognostic value of IGFBP-2 in patients with AMI-CS. - Methods - This study is a post-hoc analysis of the randomized multicentre CULPRIT-SHOCK trial. IGFBP-2 levels were measured in serum samples from 423 patients using commercially available enzyme-linked immunosorbent assay (ELISA) kits. Associations of IGFBP-2 with 30-day and one-year mortality were investigated. - Results - Median IGFBP-2 concentration was 415 ng/ml (IQR 274-699 ng/ml). Patients with IGFBP-2 ≥ median demonstrated higher 30-day (54 % vs. 37 %; p < 0.001) and one-year mortality (60 % vs. 42 %; p < 0.001) compared to the < median group. Higher IGFBP-2 concentrations were associated with increased 30-day and one-year mortality, irrespective of it being analysed as continuous or categorical variable (per 100 ng/ml IGFBP-2, hazard ratio (HR) 1.06; 95 % confidence interval (CI) 1.04-1.09; p < 0.001, respectively; IGFBP-2 ≥ vs. < median, HR 1.70, 95 % CI 1.23-2.35, p = 0.001 and HR 1.72, 95 %CI 1.27-2.33, p < 0.001). Furthermore, IGFBP-2 ≥ median was associated with increased 30-day (HR 1.70; 95 %CI 1.23-2.35; p = 0.001) and one-year mortality (HR 1.72; 95 %CI 1.27-2.33; p < 0.001), even after adjustment for established prognostic factors. - Conclusions - In AMI-CS, elevated levels of IGFBP-2 were associated with higher mortality at 30 days and one year after admission. IGFBP-2 represents a promising prognostic biomarker and could add value to risk stratification in this high-risk patient cohort, potentially informing early clinical decision-making.
Online verfügbar: 9.Oktober 2025, Artikelversion: Oktober 2025
Gesehen am 02.12.2025